A Cost effective use of computer aided technologies and integration methods in small and medium sized companies : IFAC workshop, Vienna, Austria, 7-8 September 1992 - Kopacek, Peter (Published for the International Federation of Automatic Control by Pergamon Press, 1993)
The objective of this 1st Workshop was to bring together end-users, manufacturers and (computer) control specialists to evaluate possibilities in the important field of factory automation. This volume offers solutions for product, process design, production design and control. Technical criteria are also discussed and economic justification methods are evaluated. The papers included present intelligent, modular, "low cost" approaches or solutions appropriate for small and medium sized companies which might benefit from improved efficiency and competitiveness